A Frame Synchronization Algorithm Based on LLR Threshold of LDPC Decoding Value - Zhixiong Chen; Dongsheng Han; Hongyin Xiang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
A LDPC code-aided frame synchronization algorithm based on likelihood ratio value threshold is proposed and analyzed in this paper. For soft information vectors with different frame offsets, the likelihood ratio value presenting the probability ratio of satisfaction of all check restrictions and dissatisfaction of all check restrictions are computed respectively, and then the point larger than a threshold is chosen as the final frame synchronization bounder. The method to select the threshold is studied theoretically and is analyzed according to simulation result. And Frame synchronization error ratio of new algorithm is derived. Compared to exiting LDPC code-aided frame synchronization algorithm based on maximum LLR, new algorithm saves synchronization searching time. Synchronization performance simulation results of new algorithm are given and analyzed.  DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3721